IMPACT OF SHIFT IN FOCUS OF ATTENTION ON LEARNING TABLE TENNIS BACKHAND WITH SELF-TALK IN HIGH SCHOOL FEMALES STUDENTS - Mohamadi, Ghazal; Shojaee, Masoome; Daneshfar, Afkham; Nili Ahmadabad, Zahra (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Aim: The purpose of the present study was to investigate the effect of variability of attentional focus distance by self-talk on the learning of table tennis backhand. Methods: Therefore, 80 high school girls by mean age 16(+-0/62) yr. were randomly selected from sport school of Sanandaj and assigned to 5 groups. After pretest, the participants performed 180 forehand strokes during 6 sessions with repeating the words *slightly rotation* in the internal focus group *slightly open* in the near external focus group, *over the net* in the far external focus group, and each of the words *slightly rotation, slightly open, and over the net* respectively in each 2 sessions in the increasing distance of attentional focus group. Control group performed without self-talk during acquisition phase. Retention test was performed 48 hours after acquisition test in the same situation without self-talk, and after half an hour break, transfer test was done by changing the direction of target (parallel forehand) without self-talk. The accuracy and the pattern of forehand strokes were measured by a 5 point-scale (Liao and Masters, 2001) and researcher-made scale, respectively. At the end of acquisition phase, participants filled out the frequency and self-talk beliefs questionnaire. Results: According to the results of 2-factor mixed ANOVA, acquisition, retention, and transfer of backhand accuracy in internal focus of attention group were significantly lower than other groups (p<0.05). Furthermore, the effect of increasing attentional focus distance on acquisition of backhand pattern was significant. The effect of near external attentional focus on retention of pattern was significant. But transfer of stroke pattern in control group was significantly more than far external focus group (p<0.05). Conclusions: Thus, it is recommended to use self-talk by increasing attentional focus and near external attentional focus and not to use internal focus of attention to instruct backhand to novice adolescents.